The complete mitochondrial genome of the Agrocybe aegerita, an edible mushroom. Issue 2 (20th December 2017) - Xu, Li-Ming; Hinsinger, Damien Daniel; Jiang, Guo-Feng
Abstract: Agrocybe aegerita is a medicinally and nutritionally important edible basidiomycete. Despite previous phylogenetic studies, the taxonomy of A. aegerita complex remains unclear due to lacking of resolutive data. Herein, the complete mitochondrial genome of A. aegerita is reported and analyzed. The mitogenome length was 116, 329 bp, with a GC content of 27.6%, include 17 typical protein-coding genes, two ribosomal protein genes ( rps3 ), two ribosomal RNA genes and a set of 32 transfer RNA genes. A phylogenetic analyses using complete mitogenome in Agaricales showed that A. aegerita is closely related to the genus Pleurotus and represents a clade clearly independent from other Agaricales species.